Molecular identification 16S rRNA gene of active proteolytic lactic acid bacteria (LAB) isolated from kelengkeng (Dimocarpus longan) fruit - Habibi Hidayat; WINARTO HARYADI; SABIRIN MATSJEH; TRI JOKO RAHARJO (Society for Indonesian Biodiversity, 2019)
Abstract. Hidayat H, Haryadi W, Matsjeh S, Raharjo TJ. 2019. Molecular identification 16S rRNA gene of active proteolytic lactic acid bacteria (LAB) isolated from kelengkeng (Dimocarpus longan) fruit. Biodiversitas 20: 2222-2228. Various fermentation food involves microorganisms, especially Lactic Acid Bacteria (LAB) which has beneficial properties for fermented food. The present study aims to do identification and characterization of active proteolytic LAB from kelengkeng (Dimocarpus longan), a commonly found fruit in South East Asia. From ten LAB isolates, isolates K7 and K8 appeared as basil shape based on Gram staining and were chosen for further examination. The molecular identification of these selected isolates were investigated from the 16S rRNA analysis using universal primer 27F and 1525R. The K7 and K8 isolates showed resistance ability towards acidic environment (pH 2.0) and were examined for protease enzyme screening resulting 7.5 and 6 to clear zone, which was 17 and 12 mm. The result of the molecular characterization from the two isolates indicated that isolate K7 was identified as Leuconostoc mesenteroides subsp suionicum strain LT-38 while isolate K8 was identified as Leuconostoc mesenteroides strain C305.16.